Bioplastic as well as preparation method and application thereof
By using biomass materials such as cellulose combined with toughening agents and plasticizers, the shortcomings in bioplastics in strength and impact resistance are solved, high-performance, degradable bioplastic preparation is achieved, and the problem of plastic waste is solved.
Patent Information
- Application Number
- CN202411791149.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-07
AI Technical Summary
Existing bioplastics have shortcomings in strength and impact resistance, which limits their wide application in the field of bioplastics.
The formula consisting of cellulose, toughener, plasticizer, lubricant, inorganic filler, starch and additives is used to ensure uniform dispersion of each component and good processing performance through pretreatment, mixing/heating mixing and primary processing steps.
It improves the mechanical strength, toughness and impact resistance of bioplastics, and simultaneously realizes the simultaneous occurrence of biodegradation and photodegradation, accelerates the plastic degradation process, and solves the problem of plastic waste.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of bioplastics, and in particular relates to a bioplastic, a preparation method and application thereof. Background Art
[0002] In modern society, plastic products are everywhere. Due to their excellent physical properties, diverse functions and low prices, they are widely used in agriculture, industry, construction, packaging and daily life. However, most plastic products are made of petroleum-based polymer materials, the waste products of which are difficult to decompose and the recycling rate is relatively low. As people's dependence on plastic products deepens, the amount of waste plastic is also increasing. These non-degradable plastic wastes not only pile up on land, but also flow into lakes and oceans in large quantities, posing a threat to the living environment of marine life, and even entering the human body through the food chain, posing a potential risk to human health. Traditional methods of dealing with these plastic wastes include landfilling and incineration, but these methods still cause varying degrees of pollution to the environment. Therefore, it has become particularly urgent to develop a new type of plastic material that is both environmentally friendly and economical.
[0003] As an alternative, bioplastics can be made from a variety of biomass raw materials, which helps reduce dependence on fossil fuels and lower greenhouse gas emissions. Starch, as a natural substance for making biodegradable plastic compositions, is widely used due to its excellent degradation properties, but biodegradable polymer materials made from starch and the like have some problems in terms of strength and impact resistance. Cellulose is one of the most abundant biomass-based natural polymers in nature. Compared with traditional petroleum-based polymers, cellulose is not only renewable, but also completely biodegradable, and has higher mechanical strength than starch. However, cellulose presents certain challenges during thermal processing. It easily agglomerates in the matrix polymer, which results in poor performance of bioplastics made from cellulose in terms of strength and toughness, thus limiting the widespread application of cellulose in the field of bioplastics.
[0004] Therefore, it is necessary to develop a bioplastic, a preparation method and an application thereof to improve its processing performance and mechanical strength, and further meet the demand for low-cost bioplastics with biocompatibility, biodegradability and high performance. Summary of the invention
[0005] The purpose of the present invention is to overcome the above-mentioned shortcomings of cellulose in the preparation process of bioplastics and provide a bioplastic.
[0006] The present invention adopts the following technical solutions: A bioplastic is made from the following raw materials in parts by mass: 10-70 parts of cellulose, 1-10 parts of a toughening agent, 1-40 parts of a first plasticizer, 1-2 parts of a second plasticizer, 0.3-15 parts of a lubricant, 1-10 parts of an inorganic filler, 0.1-2 parts of starch, and 0.1-5 parts of an auxiliary agent, wherein the auxiliary agent includes a photodegradation activator, an ultraviolet stabilizer, and an oxidant for plastic degradation.
[0007] Specifically, cellulose, as the main biomass-based natural polymer material, can provide renewability and biodegradability. Tougheners are used to improve the toughness of bioplastics to prevent them from breaking easily when subjected to stress. The main functions of the first plasticizer and the second plasticizer are to increase the softness and plasticity of the plastic, facilitate processing and molding, and further optimize the processing performance and physical properties of the plastic. Lubricants are used to reduce friction and resistance during processing, improve production efficiency, and also help improve the surface gloss of the plastic. Inorganic fillers are used to enhance the mechanical properties and heat resistance of plastics, while reducing costs. Starch can provide renewability and biodegradability, and also help improve the dispersion processing performance of plastics. In addition, additives can improve the stability, durability of plastics during use and biodegradability when discarded.
[0008] The present invention makes full use of the natural substance of cellulose, improves the strength and impact resistance of starch, and has physical properties suitable for being a substitute raw material for plastics. While reducing the manufacturing cost, biodegradation and photodegradation can occur simultaneously to accelerate the degradation of plastics, thereby solving the problem of plastic waste.
[0009] The cellulose includes one or more of wood powder, rice husk, corn stalks, and reeds.
[0010] Furthermore, the purpose of the present invention is to utilize wood flour and porous herbaceous agricultural wastes such as grain husks and grain straws, and at the same time utilize waste resources, solve the problem of poor strength and impact resistance of starch plastics by utilizing these cellulose binding tissues.
[0011] Specifically, wood powder has high strength and hardness, which can enhance the mechanical properties of bioplastics; rice husks are rich in silicon, which helps to improve the heat resistance and stability of bioplastics; the cellulose in corn stalks has a unique structure, which can improve the processing fluidity and toughness of bioplastics; and reeds, due to their good fiber arrangement and high specific surface area, help to improve the tensile strength and wear resistance of bioplastics.
[0012] The toughening agent includes one or more of styrene-butadiene block copolymer, thermoplastic polyurethane elastomer, thermoplastic polyolefin elastomer, thermoplastic elastomer, thermoplastic vulcanized rubber, and hydrogenated styrene-ethylene / butylene-styrene block copolymer.
[0013] Specifically, styrene-butadiene block copolymers and hydrogenated styrene-ethylene / butylene-styrene block copolymers have good elastic recovery and weather resistance, and can significantly improve the flexibility and aging resistance of bioplastics; thermoplastic polyurethane elastomers have excellent wear resistance, tear resistance and oil resistance, and can improve the mechanical properties of bioplastics; thermoplastic polyolefin elastomers and thermoplastic elastomers have low cost and good processing performance, and can reduce production costs while maintaining the performance of bioplastics; and thermoplastic vulcanizates combine the elasticity of rubber and the processability of plastics, and can provide bioplastics with excellent impact resistance and chemical corrosion resistance.
[0014] The first plasticizer includes low molecular weight polypropylene or starch plastic, and the second plasticizer is low molecular weight polyethylene.
[0015] Specifically, low molecular weight polypropylene has good fluidity and processing properties, which can effectively reduce the melt viscosity of bioplastics and improve their fluidity during processing, thus facilitating molding and processing. At the same time, low molecular weight polypropylene can also form good compatibility with biomass raw materials such as cellulose, which can improve the flexibility of cellulose-based bioplastics and help improve the overall performance of bioplastics.
[0016] Specifically, the low molecular weight polypropylene is modified polypropylene, and its preparation method is as follows: N1: Add 100 parts of low molecular weight polypropylene into a high-speed mixer, add 10 parts of acrylic acid and 10 parts of glycidyl methacrylate respectively, and finally add 1 part of benzoyl peroxide. Use a high-speed mixer to mix all the raw materials evenly. The mixing time is about 10-15 minutes to ensure that all components are fully dispersed.
[0017] N2: Add the mixed raw materials into a twin-screw extruder, set the temperature gradient of the twin-screw extruder, feed zone: 160-180°C, middle zone: 180-200°C, discharge zone: 200-220°C, set the screw speed to 200-300 rpm to ensure that the materials are fully mixed and reacted in a molten state, the reaction time is 3-5 minutes, the extruded material is cooled and solidified to form a strip or granular graft copolymer, and dried in a drying oven at 60-100°C for 4-8 hours until the water content is less than 5%.
[0018] Specifically, carboxyl, hydroxyl and epoxy groups of acrylic acid and methacrylate glycidyl are introduced into the molecular chain of the grafted low-molecular-weight polypropylene. These polar functional groups can form hydrogen bonds, covalent bonds and other interactions with other components in bioplastics, such as hydroxyl groups on the surface of biomass materials such as cellulose and starch, thereby significantly improving the compatibility between low-molecular-weight polypropylene and these components, allowing each component to be more evenly dispersed in the bioplastic, forming a stable microstructure, reducing phase separation, and improving the overall performance stability of the bioplastic.
[0019] On the one hand, the introduction of grafted monomers increases the flexibility and polarity of the low-molecular-weight polypropylene molecular chain, enhances its binding force with other components, and can better transmit stress when subjected to external forces, thereby improving the toughness and impact resistance of bioplastics; on the other hand, low-molecular-weight polypropylene itself has a certain strength. After grafting modification, its synergistic effect with other reinforcing phases is more significant, further improving the tensile strength and modulus of bioplastics. The fluidity and thermal stability of grafted low-molecular-weight polypropylene are improved, and the structural changes of its molecular chain make it easier to flow at high temperatures during processing, which can better fill the mold cavity and reduce the difficulty of processing and molding. At the same time, the introduction of polar functional groups increases its friction with the surface of the processing equipment and reduces the slippage of the material during processing, which is conducive to improving processing accuracy and production efficiency, reducing the defective rate, and reducing production costs. The grafting of monomers such as acrylic acid and glycidyl methacrylate has changed the chemical structure of low-molecular-weight polypropylene to a certain extent, making it easier to be decomposed by microorganisms. These grafted monomers and their introduced functional groups may become active sites for microbial attack, accelerating the degradation process of low-molecular-weight polypropylene, thereby increasing the biodegradation rate of the entire bioplastic.
[0020] Low molecular weight polyethylene has excellent fluidity and processing properties. Compared with the first plasticizer, the molecular chain of low molecular weight polyethylene is shorter and it is easier to penetrate into the molecular gaps of biomass raw materials such as cellulose, thereby achieving a better plasticizing effect. At the same time, low molecular weight polyethylene can also work synergistically with the first plasticizer to further reduce the melt viscosity of bioplastics and improve their processing properties and physical properties.
[0021] Specifically, the low molecular weight polyethylene is modified polyethylene, and its preparation method is as follows: N1: Add 100 parts of low molecular weight polyethylene, 2 parts of vinyl trimethoxysilane, and 0.5 parts of benzoyl peroxide into a high-speed mixer, use the high-speed mixer to mix all the raw materials evenly, and stir at a speed of 500-1000 rpm at room temperature for 5-15 minutes to ensure that all components are fully dispersed.
[0022] N2: Add the mixed raw materials into a twin-screw extruder, set the temperature gradient of the twin-screw extruder, feed zone: 150-160°C, middle zone: 170-180°C, discharge zone: 190-200°C, set the screw speed to 50-150 rpm to ensure that the materials are fully mixed and reacted in a molten state, the reaction time is 10-30 minutes, the extruded material is cooled and solidified to form a strip or granular graft copolymer, and dried in a drying oven at 60-100°C for 4-8 hours until the water content is less than 5%.
[0023] The free radicals generated by the decomposition of benzoyl peroxide can trigger the cross-linking reaction of low molecular weight polyethylene, forming a three-dimensional network structure between the molecular chains. The cross-linking temperature of benzoyl peroxide and low molecular weight polyethylene is around 140-180°C. The low molecular weight polyethylene cross-linked by benzoyl peroxide has significantly improved hardness and tensile strength.
[0024] When vinyl trimethoxysilane is used for cross-linking modification of low molecular weight polyethylene, the vinyl group in its molecule can undergo a grafting reaction with the molecular chain of low molecular weight polyethylene, and the silane oxy group can form chemical bonds with other substances after hydrolysis. The low molecular weight polyethylene cross-linked with vinyl trimethoxysilane has good water resistance, adhesion and flexibility.
[0025] Starch plastic, as a natural polymer material, has similar chemical structure and properties to cellulose. The addition of starch plastic can not only increase the biomass content of bioplastics, but also improve its biodegradability and renewability.
[0026] The preparation method of modified starch plastic comprises the following steps: P1. Mix starch with deionized water to prepare starch milk with a mass fraction of 17%-23%, stir evenly to fully disperse starch particles in water to avoid agglomeration, increase the contact area with other substances, and facilitate the uniform reaction. Use a sodium hydroxide solution with a concentration of 1-3 mol / L to adjust the pH of the starch milk to 8-9 to activate the hydroxyl groups in the starch molecules, making it easier to undergo esterification reaction with octenyl succinic anhydride, thereby improving the reaction efficiency and the degree of substitution of the product. According to the ratio of starch to octenyl succinic anhydride mass ratio of 100:1-3, octenyl succinic anhydride is slowly added dropwise to the starch milk, and stirred continuously at 33℃-37℃ for 2.5h-3.5h to make the reaction fully proceed. Too high temperature may lead to increased side reactions or starch gelatinization, and too low temperature will result in too slow reaction rate. Continuous stirring helps the uniform dispersion of octenyl succinic anhydride in the starch milk, so that it can fully contact with starch molecules, improve the reaction efficiency and product uniformity. After the reaction is completed, the pH of the reaction system is adjusted to 6-7 with a hydrochloric acid solution with a concentration of 1-3mol / L to terminate the reaction. The reaction solution is filtered or centrifuged, and the obtained precipitate is repeatedly washed with deionized water until neutral, and then dried at 35℃-39℃ for 11h-13h, and finally passed through a 180-220 mesh sieve to obtain esterified modified starch.
[0027] P2. Put polylactic acid, polyvinyl alcohol and esterified modified starch into a high mixer and mix for 5-10 minutes. Polylactic acid has good biocompatibility, mechanical properties and processing properties. Polyvinyl alcohol has excellent water solubility, film-forming properties and adhesion, which complement the hydrophobicity and thermal stability of esterified modified starch. After the three components are blended, they can give full play to their respective advantages to form a mixed system with more balanced performance and better comprehensive performance, thereby improving the mechanical strength, flexibility, heat resistance and processing properties of modified starch plastics. Add dispersant stearic acid and continue blending for 5-10 minutes. Stearic acid as a dispersant can reduce the surface tension between the components and prevent the occurrence of agglomeration, so that polylactic acid, polyvinyl alcohol and esterified modified starch are more evenly dispersed during the mixing process, further improving the mixing effect and the performance stability of the material. At the same time, stearic acid can also play a certain lubricating role, improve the processing fluidity of the material, reduce the difficulty of processing, and improve production efficiency. Add the crosslinking agent N, N'methylenebisacrylamide and mix for 3-5 minutes to form a mixed raw material. N,N'methylenebisacrylamide is used as a crosslinking agent. During the mixing process, it can undergo a crosslinking reaction with the active groups on the molecular chains of polylactic acid, polyvinyl alcohol and esterified modified starch to form a three-dimensional network structure. This crosslinking structure can significantly improve the strength, hardness and heat resistance of the modified starch plastic, while also enhancing the water resistance and solvent resistance of the material. The mixed raw materials are then put into a twin-screw granulator for extrusion and granulation to form a degradable starch plastic.
[0028] The lubricant includes 1-5 parts of ester lubricant, 0.1-5 parts of wax lubricant, and 0.1-5 parts of amide lubricant. The ester lubricant includes one or more of vegetable oil, synthetic ester, and polyglycerol ester. The wax lubricant includes one or more of wax, candelilla wax, carnauba wax, soybean wax, and paraffin. The amide lubricant includes one or more of oleamide, stearamide, erucamide, behenamide, and palmitamide.
[0029] Specifically, vegetable oils include rapeseed oil and soybean oil, which are not only environmentally friendly but also can provide a certain amount of biomass content for bioplastics. Synthetic esters include sebacic acid ester and azelaic acid ester, which have better thermal stability and chemical stability and can maintain their lubricating effect under high temperature and high pressure processing conditions. Polyglycerol esters include polyglycerol monostearate, which has good emulsification and lubrication effects.
[0030] Specifically, wax lubricants have a low melting point and good lubricity, which can effectively reduce the friction and resistance of bioplastics during processing and improve production efficiency. At the same time, they can also provide a certain gloss and hardness for bioplastics. Waxes include microcrystalline wax and white wax, which have good lubricity and demoulding properties, candelilla wax has good thermal stability and lubricity, carnauba wax has a high melting point and good gloss, soybean wax has good biodegradability and lubricity, and paraffin wax has good lubricity and cost advantages.
[0031] Specifically, amide lubricants have excellent lubricity and demoulding properties, and can effectively prevent adhesion and sticking during the processing of bioplastics. In addition, they can also improve the heat resistance and chemical corrosion resistance of bioplastics. Specifically, oleic acid amide has good internal and external lubricity, stearic acid amide has good thermal stability and lubricity, erucic acid amide has good lubricity and antistatic properties, behenic acid amide has good lubricity and thermal stability, and palmitamide has good lubricity and biodegradability.
[0032] The starch includes common starch or partially pregelatinized corn starch.
[0033] Specifically, common starch includes potato starch and wheat starch. The addition of common starch can increase the biomass content of bioplastics, while improving its biodegradability and certain film-forming properties, and can improve the flexibility and transparency of bioplastics.
[0034] Specifically, pregelatinized starch is a paste with a certain viscosity and fluidity formed by partially or completely breaking starch particles after a certain treatment. Partially pregelatinized corn starch can not only provide biomass content and biodegradability similar to ordinary starch, but also improve the processing performance of bioplastics. The addition of pregelatinized starch can reduce the melt viscosity of bioplastics and improve their fluidity, thereby facilitating molding and processing. At the same time, pregelatinized starch can also form better compatibility with other raw materials such as cellulose, which helps to improve the overall performance of bioplastics.
[0035] The inorganic filler includes a first filler, a second filler and a third filler, the first filler includes one or more of silicon dioxide, aluminum silicate, and magnesium carbonate, the second filler is calcium carbonate, and the third filler includes one or more of titanium dioxide, carbonate, phosphate, and talc.
[0036] Specifically, the first filler has excellent hardness and wear resistance, and can significantly improve the tensile strength and compressive strength of bioplastics. At the same time, they can also improve the heat resistance and chemical corrosion resistance of bioplastics, so that they maintain stable performance in high temperature and corrosive environments. Specifically, silicon dioxide has a good reinforcing effect and can improve the hardness and wear resistance of bioplastics. Aluminum silicate has good heat resistance and chemical stability, and can improve the heat resistance of bioplastics. Magnesium carbonate has good flame retardancy and heat resistance, and can improve the flame retardancy of bioplastics.
[0037] Specifically, calcium carbonate has the advantages of low cost, easy access, and good processing performance. In the formulation of bioplastics, the addition of calcium carbonate can further reduce production costs while improving the hardness and rigidity of bioplastics. In addition, calcium carbonate can also form good compatibility with other raw materials such as cellulose, which helps to improve the overall performance of bioplastics.
[0038] Specifically, titanium dioxide has excellent whiteness and hiding power, which can improve the color and appearance of bioplastics; carbonates include barium carbonate and zinc carbonate, which can improve the rigidity and dimensional stability of the material. Phosphates include calcium phosphate and aluminum phosphate, which have good flame retardancy and chemical stability and can improve the flame retardancy of bioplastics. Talc can increase the lubricity and demoulding properties of bioplastics and improve production efficiency.
[0039] The auxiliary agents include photodegradation activators, ultraviolet stabilizers, and oxidants for plastic degradation.
[0040] Specifically, the photodegradation active agent includes ferrocene. The photodegradation active agent can make bioplastics decompose faster in the natural environment, thereby reducing pollution to the environment. The photodegradation active agent can absorb light energy and convert it into chemical energy, thereby inducing the breakage and degradation of the molecular chain of bioplastics. Specifically, ferrocene can produce free radicals under ultraviolet light irradiation, and these free radicals can trigger the photodegradation reaction of plastics and accelerate its degradation process. Ferrocene is a relatively environmentally friendly compound that will not cause serious pollution to the environment. The decomposition cycle can be adjusted according to the environment so that biodegradation and photodegradation occur simultaneously.
[0041] Specifically, UV stabilizers include bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate. During the use of bioplastics, ultraviolet radiation can cause aging, discoloration, cracking and other problems on the surface of bioplastics, seriously affecting their service life and performance. UV stabilizers are used to protect bioplastics from damage by ultraviolet rays. UV stabilizers can absorb or reflect ultraviolet rays, thereby reducing their destructive effects on bioplastics. At the same time, it can also react with active groups in the molecular chain of bioplastics to form stable chemical bonds, further improving the UV resistance of bioplastics. Of course, the use of UV stabilizers is more to prevent plastics from degrading prematurely during use. UV stabilizers are compatible with other components of bioplastics and will not cause a decrease in material performance. The amount of UV stabilizer added will not significantly inhibit the biodegradation process.
[0042] Oxidants for plastic degradation include ferric sulfate and ferric citrate. Oxidants for plastic degradation can accelerate the oxidative degradation of bioplastics and make bioplastics degrade in a shorter time. Ferric sulfate and ferric citrate are relatively environmentally friendly compounds and will not cause serious pollution to the environment. When ferric sulfate reacts with polymers or other substances, it can produce free radicals with strong oxidizing properties. These free radicals can attack polymer molecular chains, trigger chain oxidation reactions, and accelerate the degradation of plastics. At the same time, the free radicals produced by ferric sulfate can further react with substances such as oxygen in the environment to generate more active oxygen species, such as hydroxyl radicals, which can also promote the degradation of plastics. Ferric citrate may have certain photocatalytic activity under light conditions. The synergistic effect of its iron ions and citrate ions enables it to absorb light energy and convert it into chemical energy, producing substances with redox activity such as electron-hole pairs, hydroxyl radicals, etc. These active substances can directly participate in the degradation reaction of plastics and improve the efficiency of photodegradation.
[0043] Furthermore, another object of the present invention is to provide a method for preparing bioplastics, comprising the following steps: S1, drying and crushing the cellulose to obtain a pretreated powder; Specifically, the cellulose is dried in a drying oven at 60-100° C. for 4-8 hours until the moisture content is less than 5%. Excessive moisture will cause agglomeration during pulverization, or affect the uniform mixing effect between the raw materials in subsequent mixing processes.
[0044] After drying, it is crushed. A crusher is used to crush the dried cellulose into fine powder with a particle size of 80-200 mesh. The crushing operation can turn the cellulose into fine particles to form pre-treated powder. Such pre-treated powder has a larger specific surface area, which is more conducive to subsequent full contact and uniform mixing with other raw materials.
[0045] In order to improve the subsequent performance of the pretreated powder, step S11 is also included, wherein the pretreated powder of step S1 is first subjected to alkali treatment, then enzymolysis, and finally dried to obtain enzymolyzed cellulose. Specifically, step S111: first directly crush the cellulose, soak the pretreated powder in 2% NaOH alkali solution at room temperature for 2 hours, repeatedly wash with clean water until neutral and dry; step S112: add 10U / g cellulase and 10U / g β-glucosidase, use 50mM citric acid buffer to mix with cellulose powder, adjust the pH value to 4.5-6.0 to form a 1-10% (w / v) suspension, enzymolyze at 40°C for 24 hours and stir every 2 hours, and then dry in a drying oven at 60-100°C for 4-8 hours.
[0046] The enzymatic hydrolysis process can destroy the crystal structure of cellulose, release more active sites, and make it easier to mix and process with other polymers. Enzymatic hydrolysis can increase the dispersibility of cellulose and reduce impurities in cellulose, such as lignin and hemicellulose, so that it can be more evenly dispersed in the bioplastic matrix, thereby improving the overall properties of the material, such as strength and toughness. Enzymatically treated cellulose is more easily decomposed by microorganisms, thereby accelerating the biodegradation process of bioplastics.
[0047] In order to improve the mixing performance of the filler, step S12 is also included. Step S12 is specifically as follows: S121, dissolving 1-2g of titanate coupling agent in 100mL of water, stirring evenly, to form a titanate coupling agent solution with a concentration of 1-2%; S122, treating 100 parts of inorganic filler and 1 part of titanate coupling agent solution in an ultrasonic treatment device at a temperature of 30-40°C and a power of 100-200W for 20-30 minutes, and using a stirrer to slowly stir during the treatment process. S123, drying in a drying oven at 60-100°C for 4-8 hours until the water content is less than 5%. The titanate coupling agent is Tyzor TPT of Dorf Ketal.
[0048] S2, mixing the pretreated powder of step S1 with part of the lubricant or the first plasticizer, and then mixing with other materials; Specifically, the pretreated powder obtained in step S1 is first mixed with a lubricant. The addition of a lubricant can improve the fluidity of the material, making subsequent mixing, processing and other operations smoother, reducing friction between materials and between materials and processing equipment, and avoiding material adhesion and other unfavorable processing situations.
[0049] Another method is to mix the pretreated powder with a first plasticizer. The first plasticizer can increase flexibility, make the material easier to shape in subsequent processing, improve the plasticity of the bioplastic, and ensure that the final product has suitable physical properties.
[0050] Specifically, in the process of manufacturing bioplastics, if cellulose is directly mixed with other materials and heated to 160-200 degrees and extruded through a screw, due to the difference in specific gravity and the fact that the cellulose powder is too fine, the evenly mixed components cannot be extruded, resulting in only fine wood powder and other powders remaining. The raw materials cannot be evenly mixed and transported, which easily clogs the extrusion screw. To solve this problem, step S2 is to first heat the cellulose and some materials to make the particles aggregate with each other, and then undergo secondary processing to manufacture bioplastics.
[0051] S3, in step S2, the pretreated powder of step S1 is first heated and mixed, and then heated and mixed with part of the lubricant into granules, and after primary processing, it is mixed with other materials, dried, extruded, and granulated to obtain bioplastics; Specifically, the pretreated powder of step S1 is first heated to 120-200°C in a twin-screw extruder and mixed for 15-35 minutes. Heating helps to break some hydrogen bonds and other forces between cellulose molecules, making its structure relatively loose, easier to blend with subsequently added substances, and improving the uniformity of mixing. At the same time, it can also activate some activities of cellulose itself, which is beneficial to subsequent reactions.
[0052] Next, it is mixed with lubricant and heated to 160-200℃ in a twin-screw extruder to ensure that the lubricant is evenly dispersed for 15-35 minutes to further optimize the material's fluidity and other properties. After such initial processing, it has better processing characteristics and is then mixed with other materials. Subsequently, it is extruded and granulated, and dried in a drying oven at 60-100℃ for 4-8 hours until the moisture content is less than 5%. Excess moisture or other volatile components are removed by drying, and finally the bioplastic product is obtained to ensure its stable quality and performance meets the requirements.
[0053] S4. In step S2, the pretreated powder of step S1 is first heated, mixed and extruded with the first plasticizer, and then mixed with other materials, extruded and granulated after initial processing, and then dried to obtain bioplastics.
[0054] First, the pre-treated powder of step S1 and the first plasticizer are heated to 160-200°C in a twin-screw extruder and preliminarily mixed for 15-35 minutes. Under the action of heating and the first plasticizer, the cellulose absorbs the plasticizer better and improves its plasticity and other properties, and then extrusion molding is performed. Extrusion molding can preliminarily process the material according to a certain shape and size, giving it a basic shape contour.
[0055] After such primary processing, it is heated to 160-200°C in a twin-screw extruder, mixed with other materials for 15-35 minutes, and then dried in a drying oven at 60-100°C for 4-8 hours until the moisture content is less than 5%. By removing excess moisture, etc., the quality of the bioplastic is guaranteed so that it can meet subsequent use needs, and finally a bioplastic product that meets the requirements is obtained.
[0056] Furthermore, another object of the present invention is to provide an application of a bioplastic, wherein the bioplastic is applied in packaging materials.
[0057] Bioplastics can be used to make beverage bottles, food packaging bags, lunch boxes and other food packaging materials. Their degradable properties allow these packaging materials to decompose faster after being discarded, reducing pollution to the environment. At the same time, bioplastics also have good barrier properties, which can effectively prevent food from oxidation and deterioration, and extend the shelf life of food.
[0058] Bioplastics can be used for packaging of daily necessities such as cosmetics, toiletries, etc., and can be processed into various exquisite shapes according to product design requirements. Their good plasticity and processability can meet diverse packaging design needs.
[0059] Bioplastics can be used in cushioning materials, packaging bags, etc. They can withstand certain pressure and impact and protect goods from damage during transportation.
[0060] The bioplastic of the present invention is mainly made of renewable and biodegradable biomass raw materials. Compared with traditional plastics, bioplastics can be decomposed by microorganisms more quickly after being discarded, and eventually converted into part of the carbon cycle in nature, thereby significantly reducing pollution to the environment. The bioplastic of the present invention is used in packaging materials and not only has excellent physical properties, but also has good environmental performance, which can reduce pollution to the environment.
[0061] Compared with the prior art, the present invention has the following advantages: 1. The present invention makes full use of the natural substance of cellulose, improves the strength and impact resistance of starch, and has physical properties suitable for being a substitute raw material for plastics. While reducing the manufacturing cost, the simultaneous occurrence of biodegradation and photodegradation can accelerate the degradation of plastics, thereby solving the problem of plastic waste.
[0062] 2. The preparation method of the present invention ensures the uniform dispersion of each component and good processing performance through pretreatment, mixing / heat mixing and primary processing steps, and obtains a bioplastic product that has excellent physical and mechanical properties, is easy to process and is environmentally friendly through secondary processing of other components. The present invention not only solves the problems of cellulose-based bioplastics in processing and performance, but also maintains its good biodegradability and environmental friendliness.
[0063] 3. The bioplastic of the present invention is mainly made of renewable and biodegradable biomass raw materials. Compared with traditional plastics, bioplastics can be decomposed by microorganisms more quickly after being discarded, and eventually converted into part of the carbon cycle in nature, thereby significantly reducing pollution to the environment. The bioplastic of the present invention is used in packaging materials and not only has excellent physical properties, but also has good environmental performance, which can reduce pollution to the environment. DETAILED DESCRIPTION
[0064] In order to make those skilled in the art more clearly understand the technical solution of the present invention, the following examples are listed for illustration. Unless otherwise specified, the raw materials, reagents or devices used in the following embodiments can be obtained from conventional commercial channels or can be obtained by existing known methods.
[0065] The present invention will be further described below in conjunction with specific embodiments: A bioplastic is made from the following raw materials in parts by mass: 10-70 parts of cellulose, 1-10 parts of a toughening agent, 1-40 parts of a first plasticizer, 1-2 parts of a second plasticizer, 0.3-15 parts of a lubricant, 1-10 parts of an inorganic filler, 0.1-2 parts of starch, and 0.1-5 parts of an auxiliary agent, wherein the auxiliary agent includes a photodegradation activator, an ultraviolet stabilizer, and an oxidant for plastic degradation.
[0066] The cellulose is made of porous herbaceous agricultural waste, including one or more of wood powder, rice husk, corn stalks and reeds.
[0067] The toughening agent includes one or more of styrene-butadiene block copolymer, thermoplastic polyurethane elastomer, thermoplastic polyolefin elastomer, thermoplastic elastomer, thermoplastic vulcanized rubber, and hydrogenated styrene-ethylene / butylene-styrene block copolymer. The styrene-butadiene block copolymer is Taiwan Rubber 3206, China, the thermoplastic polyurethane elastomer is Covestro UB90A, Germany, the thermoplastic polyolefin elastomer is LyondellBasell CA138A, the thermoplastic elastomer is German KTC5FTZ, the thermoplastic vulcanized rubber is ExxonMobil 121-70M350, and the hydrogenated styrene-ethylene / butylene-styrene block copolymer is Taiwan Rubber 7131.
[0068] The first plasticizer includes modified low molecular weight polypropylene or modified starch plastic, and the second plasticizer is modified low molecular weight polyethylene.
[0069] Low molecular weight polypropylene is modified polypropylene, and its preparation method is as follows: N1: Add 100 parts of low molecular weight polypropylene into a high-speed mixer, add 10 parts of acrylic acid and 10 parts of glycidyl methacrylate respectively, and finally add 1 part of benzoyl peroxide. Use a high-speed mixer to mix all the raw materials evenly for about 15 minutes to ensure that all components are fully dispersed.
[0070] N2: Add the mixed raw materials into a twin-screw extruder, set the temperature gradient of the twin-screw extruder, feed zone: 160-180°C, middle zone: 180-200°C, discharge zone: 200-220°C, set the screw speed to 300 rpm to ensure that the materials are fully mixed and reacted in a molten state, the reaction time is 5 minutes, the extruded material is cooled and solidified to form a strip or granular graft copolymer, and dried in a drying oven at 100°C for 8 hours until the water content is less than 5%.
[0071] Low molecular weight polyethylene is modified polyethylene, and its preparation method is as follows: N1: Add 100 parts of low molecular weight polyethylene, 2 parts of vinyl trimethoxysilane, and 0.5 parts of benzoyl peroxide into a high-speed mixer, use the high-speed mixer to mix all the raw materials evenly, and stir at a speed of 1000 rpm for 15 minutes at room temperature to ensure that all components are fully dispersed.
[0072] N2: Add the mixed raw materials into a twin-screw extruder, set the temperature gradient of the twin-screw extruder, feed zone: 150-160°C, middle zone: 170-180°C, discharge zone: 190-200°C, set the screw speed to 150 rpm to ensure that the materials are fully mixed and reacted in a molten state, the reaction time is 30 minutes, the extruded material is cooled and solidified to form a strip or granular graft copolymer, and dried in a drying oven at 100°C for 8 hours until the water content is less than 5%.
[0073] Specifically, the preparation method of modified starch plastic comprises the following steps: P1. Mix starch with deionized water to prepare a starch milk with a mass fraction of 20%, stir evenly to fully disperse the starch, adjust the pH of the starch milk to 9 with a sodium hydroxide solution with a concentration of 1 mol / L, slowly drop octenyl succinic anhydride into the starch milk according to the ratio of starch to octenyl succinic anhydride of 100:1, and continue stirring at 35°C for 2.5 hours to allow the reaction to proceed fully. After the reaction is completed, adjust the pH of the reaction system to 7 with a hydrochloric acid solution with a concentration of 1 mol / L to terminate the reaction. Filter or centrifuge the reaction solution, wash the obtained precipitate repeatedly with deionized water until it is neutral, then dry it at 37°C for 11 hours, and finally pass it through a 200-mesh sieve to obtain esterified modified starch.
[0074] P2. Put 5 parts of polylactic acid, 10 parts of polyvinyl alcohol and 70 parts of esterified modified starch into a high-speed mixer and mix for 10 minutes, add 3 parts of dispersant stearic acid and continue to blend for 10 minutes, add 2 parts of cross-linking agent N, N'methylenebisacrylamide and mix for 5 minutes to form a mixed raw material. Put the mixed raw material into a twin-screw granulator and extrude it at 180-200°C to granulate it to form a degradable modified starch plastic.
[0075] The lubricant includes 1-5 parts of ester lubricant, 0.1-5 parts of wax lubricant, and 0.1-5 parts of amide lubricant. The ester lubricant includes one or more of vegetable oil, synthetic ester, and polyglycerol ester. The wax lubricant includes one or more of wax, candelilla wax, carnauba wax, soybean wax, and paraffin. The amide lubricant includes one or more of oleamide, stearamide, erucamide, behenamide, and palmitamide.
[0076] The vegetable oils include rapeseed oil and soybean oil, the synthetic esters include sebacate and azelaic acid esters, and the polyglycerol esters include polyglycerol monostearate.
[0077] Waxes include microcrystalline wax and white wax.
[0078] The starches include potato starch, wheat starch and pregelatinized corn starch.
[0079] The inorganic filler includes a first filler, a second filler and a third filler, the first filler includes one or more of silicon dioxide, aluminum silicate, and magnesium carbonate, the second filler is calcium carbonate, and the third filler includes one or more of titanium dioxide, carbonate, phosphate, and talc.
[0080] The carbonates include barium carbonate and zinc carbonate, and the phosphates include calcium phosphate and aluminum phosphate.
[0081] The auxiliary agents include photodegradation activators, ultraviolet stabilizers, and oxidants for plastic degradation.
[0082] Photodegradation active agents include ferrocene, UV stabilizers include bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and oxidants for plastic degradation include ferric sulfate and ferric citrate.
[0083] A method for preparing bioplastics comprises the following steps: S1, drying and crushing the cellulose to obtain a pretreated powder; Specifically, the cellulose is dried in a drying oven at 60-100° C. for 4-8 hours until the moisture content is less than 5%. After drying, the cellulose is crushed into fine powder with a particle size of 80-200 mesh using a crusher.
[0084] S2, mixing the pretreated powder of step S1 with part of the lubricant or the first plasticizer, and then mixing with other materials; S3, in step S2, the pretreated powder of step S1 is first heated and mixed, and then heated and mixed with part of the lubricant into granules, and then mixed with other materials for extrusion molding after primary processing, and then dried to obtain bioplastics; First, the pre-treated powder of step S1 is heated to 120-200°C in a twin-screw extruder for mixing for 15-35 minutes, then mixed with the lubricant, heated and mixed in a twin-screw extruder to 160-200°C, ensuring that the lubricant is evenly dispersed for 15-35 minutes, and then mixed with other materials. After mixing, it is dried in a drying oven at 60-100°C for 4-8 hours until the water content is less than 5%.
[0085] S4. In step S2, the pretreated powder of step S1 and the first plasticizer are first heated to 160-200° C. in a twin-screw extruder, and preliminarily mixed for 15-35 minutes, followed by extrusion molding and drying.
[0086] After such initial processing, it is heated to 160-200°C in a twin-screw extruder, mixed with other materials for 15-35 minutes for extrusion molding, and then dried in a drying oven at 60-100°C for 4-8 hours until the moisture content is less than 5%.
[0087] In order to improve the subsequent performance of the pretreated powder, step S11 is also included, wherein the pretreated powder of step S1 is first subjected to alkali treatment, then enzymolysis, and finally dried to obtain enzymolyzed cellulose. Specifically, step S111: first directly crush the cellulose, soak the pretreated powder in 2% NaOH alkali solution at room temperature for 2 hours, repeatedly wash with clean water until neutral and dry; step S112: add 10U / g cellulase and 10U / g β-glucosidase, use 50mM citric acid buffer to mix with cellulose powder, adjust the pH value to 4.5-6.0 to form a 1-10% (w / v) suspension, enzymolyze at 40°C for 24 hours and stir every 2 hours, and then dry in a drying oven at 60-100°C for 4-8 hours.
[0088] In order to improve the mixing performance of the filler, step S12 is also included. Step S12 is specifically as follows: S121, dissolve 1-2g of titanate coupling agent in 100mL of water, stir evenly, and form a titanate coupling agent solution with a concentration of 1-2%; S122, treat 100 parts of inorganic filler and 1 part of titanate coupling agent solution in an ultrasonic treatment device at a temperature of 30-40°C and a power of 100-200W for 20-30 minutes, and stir slowly with a stirrer during the treatment process. S123, dry in a drying oven at 60-100°C for 4-8 hours until the water content is less than 5%. The titanate coupling agent is TyzorTPT.
[0089] Table 1: Mass composition ratio of the formula
[0090] Example 1 A method for preparing bioplastics comprises the following steps: Step S111: First, cellulose is directly crushed, and the pretreated powder is soaked in a 2% NaOH solution at room temperature for 2 hours, and then repeatedly washed with purified water until it becomes neutral and dried; Step S112: Add 10 U / g of cellulase and 10 U / g of β-glucosidase, mix with cellulose powder using 50 mM citric acid buffer, adjust the pH value to 4.5 to form a 5% (w / v) suspension, perform enzymolysis at 40°C for 24 hours with stirring every 2 hours, and then dry in a drying oven at 80°C for 6 hours.
[0091] S121, dissolving 2 g of titanate coupling agent in 100 mL of water, stirring evenly to form a titanate coupling agent solution with a concentration of 2%; S122. Treat 100 parts of inorganic filler and 1 part of titanate coupling agent solution in an ultrasonic treatment device at a temperature of 40° C. and a power of 150 W for 30 minutes, stirring slowly with a stirrer during the treatment.
[0092] S123. Dry in a drying oven at 100°C for 6 hours until the moisture content is less than 5%.
[0093] S1, crushing the dried cellulose to obtain pretreated powder; The dried cellulose was crushed into fine powder using a crusher with a particle size of 100 mesh.
[0094] S2. First, the pretreated powder of step S1 and the first plasticizer are heated to 200° C. in a twin-screw extruder, and preliminarily mixed for 35 minutes, followed by extrusion molding and drying.
[0095] After this initial processing, it is heated to 200°C in a twin-screw extruder, mixed with other materials for 35 minutes for extrusion molding, and then dried in a drying oven at 80°C for 6 hours until the moisture content is less than 5%.
[0096] Example 2 A method for preparing bioplastics comprises the following steps: Step S111: First, directly crush the cellulose, soak the pretreated powder in 2% NaOH alkaline solution at room temperature for 2 hours, repeatedly wash with clean water until neutral and dry; Step S112: Add 10U / g cellulase and 10U / g β-glucosidase, use 50mM citric acid buffer to mix with cellulose powder, adjust the pH value to 5.0 to form a 10% (w / v) suspension, enzymolyze at 40°C for 24 hours and stir every 2 hours, and then dry in a drying oven at 60°C for 8 hours.
[0097] Step S121, dissolving 1 g of titanate coupling agent in 100 mL of water, stirring evenly to form a titanate coupling agent solution with a concentration of 1%; S122. Treat 100 parts of inorganic filler and 1 part of titanate coupling agent solution in an ultrasonic treatment device at a temperature of 30° C. and a power of 100 W for 20 minutes, stirring slowly with a stirrer during the treatment.
[0098] S123. Dry in a drying oven at 60°C for 8 hours until the moisture content is less than 5%.
[0099] S1, crushing the dried cellulose to obtain pretreated powder; The dried cellulose was crushed into fine powder using a crusher with a particle size of 200 mesh.
[0100] S2, firstly, the pre-treated powder of step S1 is heated to 200°C in a twin-screw extruder for mixing for 15 minutes, then, it is mixed with a lubricant, heated and mixed in a twin-screw extruder to 200°C, ensuring that the lubricant is evenly dispersed for 15 minutes, and then mixed with other materials. After mixing, it is dried, and then dried in a drying oven at 60°C for 8 hours until the water content is less than 5%.
[0101] Example 3 A method for preparing bioplastics comprises the following steps: Step S111: First, directly crush the cellulose, soak the pretreated powder in 2% NaOH alkaline solution at room temperature for 2 hours, repeatedly wash with clean water until neutral and dry; Step S112: Add 10U / g cellulase and 10U / g β-glucosidase, use 50mM citric acid buffer to mix with cellulose powder, adjust the pH value to 5.0 to form a 1% (w / v) suspension, enzymolyze at 40°C for 24 hours and stir every 2 hours, and then dry in a drying oven at 100°C for 4 hours.
[0102] Step S121, dissolving 2 g of titanate coupling agent in 100 mL of water, stirring evenly to form a titanate coupling agent solution with a concentration of 2%; S122. Treat 100 parts of inorganic filler and 1 part of titanate coupling agent solution in an ultrasonic treatment device at a temperature of 40° C. and a power of 200 W for 30 minutes, stirring slowly with a stirrer during the treatment.
[0103] S123. Dry in a drying oven at 60°C for 8 hours until the moisture content is less than 5%.
[0104] S1, crushing the dried cellulose to obtain pre-treated powder; The dried cellulose was crushed into fine powder using a crusher with a particle size of 80 mesh.
[0105] S4, firstly, the pretreated powder of step S1 and the first plasticizer are heated to 160° C. in a twin-screw extruder, and preliminarily mixed for 35 minutes, and then extruded and dried.
[0106] After this initial processing, it is heated to 200°C in a twin-screw extruder, mixed with other materials for 15 minutes for extrusion molding, and then dried in a drying oven at 80°C for 8 hours until the moisture content is less than 5%.
[0107] Example 4 A method for preparing bioplastics comprises the following steps: Step S111: First, directly crush the cellulose, soak the pretreated powder in 2% NaOH alkaline solution at room temperature for 2 hours, repeatedly wash with clean water until neutral and dry; Step S112: Add 10U / g cellulase and 10U / g β-glucosidase, use 50mM citric acid buffer to mix with cellulose powder, adjust the pH value to 4.5 to form an 8% (w / v) suspension, enzymolyze at 40°C for 24 hours and stir every 2 hours, and then dry in a drying oven at 100°C for 4 hours.
[0108] Step S121, dissolving 2 g of titanate coupling agent in 100 mL of water, stirring evenly to form a titanate coupling agent solution with a concentration of 2%; S122. Treat 100 parts of inorganic filler and 1 part of titanate coupling agent solution in an ultrasonic treatment device at a temperature of 40°C and a power of 200W for 30 minutes, stirring slowly with a stirrer during the treatment. S123. Dry in a drying oven at 100°C for 4 hours until the water content is less than 5%.
[0109] S1, crushing the dried cellulose to obtain pretreated powder; The dried cellulose was crushed into fine powder with a particle size of 150 mesh using a crusher.
[0110] S2, firstly, the pre-treated powder of step S1 is heated to 120°C in a twin-screw extruder for mixing for 35 minutes, then mixed with a lubricant, heated and mixed in a twin-screw extruder to 160°C, ensuring that the lubricant is evenly dispersed for 35 minutes, and then mixed with other materials. After mixing, drying is performed, and then drying is performed in a drying oven at 100°C for 4 hours until the water content is less than 5%.
[0111] Example 5 A method for preparing bioplastics comprises the following steps: Step S111: First, cellulose is directly crushed, and the pretreated powder is soaked in a 2% NaOH solution at room temperature for 2 hours, and then repeatedly washed with purified water until it becomes neutral and dried; Step S112: Add 10 U / g of cellulase and 10 U / g of β-glucosidase, mix with cellulose powder using 50 mM citric acid buffer, adjust the pH value to 6.0 to form a 1-10% (w / v) suspension, perform enzymolysis at 40°C for 24 hours with stirring every 2 hours, and then dry in a drying oven at 60°C for 8 hours.
[0112] Step S121, dissolving 1 g of titanate coupling agent in 100 mL of water, stirring evenly to form a titanate coupling agent solution with a concentration of 1%; S122. Treat 100 parts of inorganic filler and 1 part of titanate coupling agent solution in an ultrasonic treatment device at a temperature of 30° C. and a power of 100 W for 30 minutes, stirring slowly with a stirrer during the treatment.
[0113] S123. Dry in a drying oven at 60°C for 8 hours until the moisture content is less than 5%.
[0114] S1, crushing the dried cellulose to obtain pretreated powder; The dried cellulose was crushed into fine powder using a crusher with a particle size of 200 mesh.
[0115] Step S2: First, the pretreated powder of step S1 and the first plasticizer are heated to 160° C. in a twin-screw extruder, and preliminarily mixed for 35 minutes, followed by extrusion molding and drying.
[0116] After this initial processing, it is heated to 200°C in a twin-screw extruder, mixed with other materials for 15 minutes for extrusion molding, and then dried in a drying oven at 60°C for 8 hours until the moisture content is less than 5%.
[0117] Comparative Example 1 The main difference between Comparative Example 1 and Example 1 is that Step S11 and Step S12 are omitted in Comparative Example 1. The remaining steps and component parameters of Comparative Example 1 are the same as those of Example 1.
[0118] Comparative Example 2 The main difference between Comparative Example 2 and Example 2 is that Step S11 and Step S12 are omitted in Comparative Example 2. The remaining steps and component parameters of Comparative Example 2 are the same as those of Example 2.
[0119] Comparative Example 3 The main difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, the modified low molecular weight polypropylene is completely replaced with commercially available Total 1571 polypropylene. The remaining steps and component parameters of Comparative Example 3 are the same as those of Example 1.
[0120] Comparative Example 4 The main difference between Comparative Example 4 and Example 4 is that the modified plastic starch is replaced with commercially available plastic starch from Tengkai Chemical in Comparative Example 4. The remaining steps and component parameters of Comparative Example 4 are the same as those of Example 4.
[0121] Comparative Example 5 The main difference between Comparative Example 5 and Example 1 is that the auxiliary agent is omitted in Comparative Example 5. The remaining steps and component parameters of Comparative Example 5 are the same as those of Example 1.
[0122] Comparative Example 6 The main difference between Comparative Example 6 and Example 1 is that cellulose is replaced by potato starch in Comparative Example 6. Step S11 is omitted, and the remaining steps and component parameters of Comparative Example 6 are the same as those of Example 1.
[0123] Comparative Example 7 The main difference between Comparative Example 7 and Example 1 is that the toughening agent is completely replaced with styrene-butadiene block copolymer in Comparative Example 7. The remaining steps and component parameters of Comparative Example 7 are the same as those of Example 1.
[0124] Comparative Example 8 The main difference between Comparative Example 8 and Example 1 is that the lubricant is completely replaced with rapeseed oil in Comparative Example 8. The remaining steps and component parameters of Comparative Example 8 are the same as those of Example 1.
[0125] Comparative Example 9 The main difference between Comparative Example 9 and Example 1 is that the preparation method in Comparative Example 9 is modified as follows: A method for preparing bioplastics comprises the following steps: Step S111: First, cellulose is directly crushed, and the pretreated powder is soaked in a 2% NaOH solution at room temperature for 2 hours, and then repeatedly washed with purified water until it becomes neutral and dried; Step S112: Add 10 U / g of cellulase and 10 U / g of β-glucosidase, mix with cellulose powder using 50 mM citric acid buffer, adjust the pH value to 4.5 to form a 5% (w / v) suspension, perform enzymolysis at 40°C for 24 hours with stirring every 2 hours, and then dry in a drying oven at 80°C for 6 hours.
[0126] S121, dissolving 2 g of titanate coupling agent in 100 mL of water, stirring evenly to form a titanate coupling agent solution with a concentration of 2%; S122. Treat 100 parts of inorganic filler and 1 part of titanate coupling agent solution in an ultrasonic treatment device at a temperature of 40° C. and a power of 150 W for 30 minutes, stirring slowly with a stirrer during the treatment.
[0127] S123. Dry in a drying oven at 100°C for 6 hours until the moisture content is less than 5%.
[0128] S1, crushing the dried cellulose to obtain pretreated powder; The dried cellulose was crushed into fine powder using a crusher with a particle size of 100 mesh.
[0129] S2. The pretreated powder of step S1 is mixed with other components in a twin-screw extruder and heated to 200° C. for 35 minutes, followed by extrusion molding, and then drying in a drying oven at 80° C. for 6 hours until the moisture content is less than 5%.
[0130] The component parameters of Comparative Example 9 are the same as those of Example 1.
[0131] Comparative Example 10 The main difference between Comparative Example 10 and Example 2 is that the preparation method in Comparative Example 10 is modified as follows: A method for preparing bioplastics comprises the following steps: Step S111: First, directly crush the cellulose, soak the pretreated powder in 2% NaOH alkaline solution at room temperature for 2 hours, repeatedly wash with clean water until neutral and dry; Step S112: Add 10U / g cellulase and 10U / g β-glucosidase, use 50mM citric acid buffer to mix with cellulose powder, adjust the pH value to 5.0 to form a 10% (w / v) suspension, enzymolyze at 40°C for 24 hours and stir every 2 hours, and then dry in a drying oven at 60°C for 8 hours.
[0132] Step S121, dissolving 1 g of titanate coupling agent in 100 mL of water, stirring evenly to form a titanate coupling agent solution with a concentration of 1%; S122. Treat 100 parts of inorganic filler and 1 part of titanate coupling agent solution in an ultrasonic treatment device at a temperature of 30° C. and a power of 100 W for 20 minutes, stirring slowly with a stirrer during the treatment.
[0133] S123. Dry in a drying oven at 60°C for 8 hours until the moisture content is less than 5%.
[0134] S1, crushing the dried cellulose to obtain pretreated powder; The dried cellulose was crushed into fine powder using a crusher with a particle size of 200 mesh.
[0135] S2, heating the pretreated powder of step S1 to 200° C. in a twin-screw extruder and mixing for 15 minutes, then mixing it with other components, heating and mixing in a twin-screw extruder to 200° C. for extrusion molding, and drying in a drying oven at 60° C. for 8 hours until the water content is less than 5%.
[0136] The component parameters of Comparative Example 10 are the same as those of Example 2.
[0137] Performance tests were performed on the above embodiments and comparative examples, wherein the test speed of the tensile strength, elongation, and tensile elastic modulus was 5 mm / min (elastic modulus: 1 mm / min), and when the bending strength and curvature elastic modulus were tested, the distance between the supports was 62 mm, and the test speed was 1.6 mm / min.
[0138] The bioplastic material prepared by the present invention is tested for its biodegradability after 52 days by a degradation instrument and an air compressor using the detection method of GB / T 19277.1-2011, wherein the reference material is thin layer chromatography grade cellulose, the compost age is 3 months, the test container has a volume of 2.5 L, the maximum surface area of the prepared bioplastic material does not exceed 2 cmX2 cm, the reference material is used directly, and the compost is screened with a 0.5 cm sieve after removing large inert substances, the pH is 7.86, and the dry weight ratio of the compost and the bioplastic material / reference material in each compost container is 6:1.
[0139] The test data are shown in Table 2 and Table 3: Table 2: Performance test results of Examples 1-5
[0140] Table 3: Performance test results of comparative examples 1-10
[0141] Specifically, the degradation rates of Examples 1-5 after 52 days are 63.4%, 62.2%, 62.5%, 63.2%, and 63.5%, and Examples 1-5 show good mechanical properties, temperature resistance, and degradation performance. As can be seen from Table 2, Examples 1-5 make full use of the natural substances of cellulose, improve the strength and impact resistance of starch, and have physical properties suitable for use as a substitute raw material for plastics. While reducing manufacturing costs, biodegradation and photodegradation occur simultaneously to accelerate plastic degradation, thereby solving the problem of plastic waste. The preparation method of Examples 1-5 ensures uniform dispersion and good processing performance of each component through pretreatment, mixing / heat mixing, and primary processing steps, and prepares a bioplastic product having excellent physical and mechanical properties, easy processing, and environmentally friendly through secondary processing of other components. Examples 1-5 not only solve the problems of processing and performance of cellulose-based bioplastics, but also maintain their good biodegradability and environmental friendliness.
[0142] As shown in Table 3, the degradation rate of Comparative Example 1 after 52 days is 62.2%. Compared with Example 1, Comparative Example 1 does not use steps S11 and S12. Step S11 can improve the dispersibility, overall strength and dispersibility of the pretreated powder, and step S12 can improve the dispersibility of the inorganic filler. The mechanical properties and temperature resistance of Comparative Example 1 are worse than those of Example 1.
[0143] The degradation rate of Comparative Example 2 after 52 days is 61.4%. Compared with Example 2, Comparative Example 2 does not use steps S11 and S12. Step S11 can improve the dispersibility, overall strength and decomposition performance of the pretreated powder, and step S12 can improve the dispersibility of the inorganic filler. The mechanical properties and temperature resistance of Comparative Example 2 are worse than those of Example 2.
[0144] The degradation rate of Comparative Example 3 after 52 days is 61.0%. Compared with Example 1, Comparative Example 3 replaces all the modified low-molecular-weight polypropylene with commercially available low-molecular-weight polypropylene. The modified low-molecular-weight polypropylene can enhance mechanical properties, improve processing properties, and promote biodegradability. Therefore, the mechanical properties, degradation properties, and temperature resistance of Comparative Example 3 are worse than those of Example 1.
[0145] The degradation rate of Comparative Example 4 after 52 days is 60.2%. Compared with Example 4, Comparative Example 4 replaces the modified plastic starch with commercially available ordinary plastic starch. The modified plastic starch can improve the mechanical properties, improve the processing performance, and promote biodegradability. Therefore, the mechanical properties, degradation performance, and temperature resistance of Comparative Example 4 are worse than those of Example 4.
[0146] The degradation rate of Comparative Example 5 after 52 days is 54.2%. Compared with Example 1, Comparative Example 5 omits the auxiliary agent. The photodegradation active agent and the oxidant for plastic degradation can promote biodegradability. Therefore, the degradation performance of Comparative Example 5 is worse than that of Example 1.
[0147] The degradation rate of Comparative Example 6 after 52 days is 66.3%. Compared with Example 1, Comparative Example 6 replaces cellulose with starch. The mechanical strength of cellulose is stronger than that of starch, so the mechanical properties of Comparative Example 6 are worse than those of Example 1.
[0148] The degradation rate of Comparative Example 7 after 52 days is 62.3%. Compared with Example 1, Comparative Example 7 changes all toughening agents to styrene-butadiene block copolymers. The toughening effect of Example 1 is stronger than that of the single styrene-butadiene block copolymer of Comparative Example 7, so the mechanical properties of Comparative Example 7 are worse than those of Example 1.
[0149] The degradation rate of Comparative Example 8 after 52 days is 62.1%. Compared with Example 1, Comparative Example 8 changes all lubricants to rapeseed oil. The lubricating effect of Example 1 is stronger than the single benzene rapeseed oil of Comparative Example 8, and the dispersibility and mechanical properties of Example 1 are better. Therefore, the processing performance and mechanical properties of Comparative Example 8 are worse than those of Example 1.
[0150] The degradation rate of Comparative Example 9 after 52 days is 62.3%. Compared with Example 1, Comparative Example 9 mixes all the materials. Due to the difference in specific gravity and the fact that the cellulose powder is too fine, the evenly mixed components cannot be extruded, resulting in only fine powders such as wood powder remaining, which easily clog the extrusion screw, resulting in poor processing performance and dispersion effect. Therefore, the processing performance and mechanical properties of Comparative Example 9 are worse than those of Example 1.
[0151] The degradation rate of Comparative Example 10 after 52 days is 61.3%. Compared with Example 2, Comparative Example 10 mixes all the materials. Due to the difference in specific gravity and the fact that the cellulose powder is too fine, the evenly mixed components cannot be extruded, resulting in only fine powders such as wood powder remaining, which easily clog the extrusion screw, resulting in poor processing performance and dispersion effect. Therefore, the processing performance and mechanical properties of Comparative Example 10 are worse than those of Example 2.
[0152] The above is a preferred embodiment of the present invention. Relevant personnel in this technical field may make several improvements and modifications without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A bioplastic, characterized in that: The invention is prepared from the following raw materials in parts by weight: 10-70 parts of cellulose, 1-10 parts of toughening agent, 1-40 parts of first plasticizer, 1-2 parts of second plasticizer, 1.2-15 parts of lubricant, 1-10 parts of inorganic filler, 0.1-2 parts of starch and 0.1-5 parts of auxiliary agents, wherein the auxiliary agents include photodegradation activator, ultraviolet stabilizer and oxidant for plastic degradation.
2. A bioplastic according to claim 1, characterized in that: The cellulose includes one or more of wood powder, rice husk, corn stalks, and reeds.
3. The bioplastic according to claim 1, characterized in that: The toughening agent includes one or more of styrene-butadiene block copolymer, thermoplastic polyurethane elastomer, thermoplastic polyolefin elastomer, thermoplastic elastomer, thermoplastic vulcanized rubber, and hydrogenated styrene-ethylene / butylene-styrene block copolymer.
4. The bioplastic according to claim 1, characterized in that: The first plasticizer includes low molecular weight polypropylene or starch plastic, and the second plasticizer is low molecular weight polyethylene.
5. The bioplastic according to claim 1, characterized in that: The lubricant includes 1-5 parts of ester lubricant, 0.1-5 parts of wax lubricant, and 0.1-5 parts of amide lubricant. The ester lubricant includes one or more of vegetable oil, synthetic ester, and polyglycerol ester. The wax lubricant includes one or more of wax, candelilla wax, carnauba wax, soybean wax, and paraffin. The amide lubricant includes one or more of oleamide, stearamide, erucamide, behenamide, and palmitamide.
6. The bioplastic according to claim 1, characterized in that: The starch includes common starch or partially pregelatinized corn starch.
7. The bioplastic according to claim 1, characterized in that: The inorganic filler includes a first filler, a second filler and a third filler, the first filler includes one or more of silicon dioxide, aluminum silicate, and magnesium carbonate, the second filler is calcium carbonate, and the third filler includes one or more of titanium dioxide, carbonate, phosphate, and talc.
8. The bioplastic according to claim 1, characterized in that: The photodegradation active agent includes ferrocene, the ultraviolet stabilizer includes bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and the oxidant for plastic degradation includes ferric sulfate and ferric citrate.
9. A method for preparing a bioplastic, comprising the bioplastic according to any one of claims 1 to 8, characterized in that: The steps include: S1, drying and crushing the cellulose to obtain a pretreated powder; S2, mixing the pretreated powder of step S1 with part of the lubricant or the first plasticizer, and then mixing with other materials; S3, in step S2, the pretreated powder of step S1 is first heated and mixed, and then heated and mixed with part of the lubricant into granules, and then mixed with other materials for extrusion molding and granulation after primary processing, and then dried to obtain bioplastics; S4. In step S2, the pretreated powder of step S1 is first heated, mixed and extruded with the first plasticizer, and then mixed with other materials for extrusion molding and granulation after initial processing, and then dried to obtain bioplastics.
10. An application of a bioplastic, comprising the bioplastic according to any one of claims 1 to 8, characterized in that: The bioplastic is used in packaging materials.
Citation Information
Cited By
Environment-friendly flowerpot and manufacturing method
CN120283561A